Fiscal Equalization, Tax Salience, and Tax Competition - Martin Altemeyer-Bartscher (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2014)
Jurisdictions that engage in inter-regional tax competition usually try to attenuate competitive pressures by substituting salient tax instruments with hidden ones. On this effect, we investigate the efficiency consequences of inter-regional tax competition and fiscal equalization in a federal system when taxpayers fail to optimally react on shrouded attributes of local tax policy. If the statuary tax rate is a relatively salient instrument and taxpayers pay low attention to the quality and the frequency of tax enforcement, the underlying substitution of tax instruments with the aim of reducing the perceived tax price may suppress the under-exploitation of tax bases that is typically triggered by fiscal equalization.
urn:nbn:de:gbv:3:2-28829
Keywords: H77; H22; H30; 330; fiscal equalization; tax salience; tax competition; fiscal federalism; tax-cutcum-base-broadening policy